Environmental remediation in foreign countries: experience of legal regulation - A. K. Akhmadiev; V. N. Ekzaryan (Известия высших учебных заведений: Геология и разведка)
Background. Environmental remediation plays an important role in mitigating or eliminating environmental damage. The worldwide experience in organising and regulating ecosystem recovery activity is of interest.Aim. An extensive comparative analysis of the particularities of legal regulation in the sphere of environmental remediation in foreign countries.Materials and methods. The study was based on three major criteria: the environmental remediation enshrined in law; the provision of the term “remediation” or its equivalent; identifying the objects of remediation. The analysis was based on the examination of the legal information registers and official government and parliament resources of over 20 countries worldwide. The study covers the period from 1970 to 2019, because since the 1970s, one can speak about the widespread implementation of environmental laws. In individual cases, the first mentioning of the current environmental law was taken as a starting point.Results. Based on the results of the study, the countries were divided into two categories. The first group was dominated by the vertical environmental legislation system and the second — by the horizontal one. The authors described the features of each group and identified the characteristic features of environmental remediation management. These features include the requirements for remediation plans, action plans enshrined in the law, introduction of special cadastre, importance ranking of remediation objects, etc. Formulating a universal interpretation of the “environmental remediation” term is another significant result of this study.Conclusions. The study showed that the need for and importance of environmental remediation is recognised worldwide. In the meantime, it is necessary to identify the principles of environmental remediation and to systematise approaches to ecosystem restoration.